082 The Association Between Excessive Daytime Sleepiness and Math Performance in Adolescents. (3rd May 2021) - Scholes, Samantha; Rao, Akhila; Somerville, Gail; Boursier, Johanne; Gruber, Reut
Abstract: Introduction: Excessive daytime sleepiness (EDS) is defined as an increased tendency to fall asleep in a setting where an individual would be expected to stay awake and alert. Previous studies have found that EDS is associated with poor academic performance but fell short of examining the associations between EDS and achievement in specific academic subjects. Academic performance in mathematics is the most prominent predictor of later success. Findings from studies examining the associations of academic achievement in math and EDS have been inconsistent as some studies have found results indicating the EDS negatively impacts math while others found no such relationship. The aim of this study was to investigate the association between EDS and performance in mathematics in high school students. It was hypothesized that higher level of reported EDS would be associated with lower grades in mathematics. Methods: 116 typically developing adolescents (38 male) between 12–17 years of age (M=13.87, SD=1.38) participated. EDS was measured by the Sleep Disorder Inventory for Students (SDIS); Academic achievement in mathematics was measured by child's report cards; Sleep was assessed for seven nights using actigraphy and sleep logs. Results: A hierarchical multiple regression analysis was conducted to examine the associations between parent-reported EDS (independent variable) and their child's academic achievement in mathematics (dependent variable) while controlling for sleep variables (bedtime, waketime, and duration) and sex. Higher levels of EDS was negatively associated with lower grades in mathematics [F(5, 109)= 3.60, p<.01; β= -0.21, p= 0.03]. Conclusion: EDS was signiﬁcantly associated with report card grades in mathematics in typically developing adolescents. Given the cross-sectional design of the study, it can not identify what led to EDS in this sample of typically developing adolescents. We propose that future studies examine potential causes for adolescents' EDS, including factors that could impair sleep quality (e.g., undiagnosed sleep disorders) or restrict sleep duration (e.g., life-style choices such as the use of electronic devices at night). This is important as it could help to identify targets for intervention aiming at decreasing EDS and ultimately improving academic performance in mathematics. Support (if any):